Experimental Verification of Optimized Multiscroll Chaotic Oscillators Based on Irregular Saturated Functions. (6th March 2018) - Muñoz-Pacheco, J. M.; Guevara-Flores, D. K.; Félix-Beltrán, O. G.; Tlelo-Cuautle, E.; Barradas-Guevara, J. E.; Volos, C. K.
Abstract : Multiscroll chaotic attractors generated by irregular saturated nonlinear functions with optimized positive Lyapunov exponent are designed and implemented. The saturated nonlinear functions are designed in an irregular way by modifying their parameters such as slopes, delays between slopes, and breakpoints. Then, the positive Lyapunov exponent is optimized using the differential evolution algorithm to obtain chaotic attractors with 2 to 5 scrolls. We observed that the resulting chaotic attractors present more complex dynamics when different patterns of irregular saturated nonlinear functions are considered. After that, the optimized chaotic oscillators are physically implemented with an analog discrete circuit to validate the use of proposed irregular saturated functions. Experimental results are consistent with MATLAB™ and SPICE circuit simulator. Finally, the synchronization between optimized and nonoptimized chaotic oscillators is demonstrated.